Using IO Table in Analyzing the Environmental Burden of PET Plastic Packaging Industry in Vietnam - Yen, Ta Thi; Anh Tuyet, Nguyen Thi (VNU Journal of Science: Earth and Environmental Sciences; Vol 36 No 2, 2020)
Plastic industry plays an important role in the economic development. The PET plastic packaging industry is the largest segment of the plastic industry, accounting for 37.43% of GDP of Vietnam's plastic industry. However, the current production and consumption of PET in Vietnam are having significant environmental impacts. This study uses input-output tables (IO tables) in 2007, 2012 and updated for 2018 to determine the current status of plastic production and plastic consumption (by economic sectors) in Vietnam during the period of 2007 - 2018. At the same time, the research integrates IO tool and LCI to identify the environmental burden in the PET plastic packaging life cycle through PET’s demand of other economic sectors. The results show that the two biggest PET plastic consumers are food processing sectors and electronics sectors, and these industries are also responsible for the highest indirect GHG emissions. This result can form the basis for developing a sustainable plastic packaging production and consumption strategy for Vietnam.